Tandem dinucleophilic cyclization of cyclohexane-1,3-diones with pyridinium salts - Kiamehr, Mostafa; Moghaddam, Firouz Matloubi; Mkrtchyan, Satenik; Semeniuchenko, Volodymyr; Supe, Linda; Villinger, Alexander; Langer, Peter; Iaroshenko, Viktor O. (Beilstein Journal of Organic Chemistry, 2013)
The cyclization of cyclohexane-1,3-diones with various substituted pyridinium salts afforded functionalized 8-oxa-10-aza-tricyclo[7.3.1.02,7]trideca-2(7),11-dienes. The reaction proceeds by regioselective attack of the central carbon atom of the 1,3-dicarbonyl unit to 4-position of the pyridinium salt and subsequent cyclization by base-assisted proton migration and nucleophilic addition of the oxygen atom to the 2-position, as was elucidated by DFT computations. Fairly extensive screening of bases and additives revealed that the presence of potassium cations is essential for formation of the product.
Keywords: cyclization; density functional calculations; heterocycles; nucleophilic addition; pyridinium salt

(untitled) - Bennasar, M.-L.; Jiménez, J.-M.; Sufi, B. A.; Bosch, J. (Tetrahedron Lett., 1996)

(untitled) - Bennasar, M.-L.; Lavilla, R.; Alvarez, M.; Bosch, J. (Heterocycles, 1988)

(untitled) - Spitzner, D.; Zaubitzer, T.; Shi, Y. J.; Wenkert, E. (J. Org. Chem., 1988)

(untitled) - Bieräugel, H.; Brands, K. M. J.; Pandit, U. K. (Heterocycles, 1988)

Advances in Nitrogen Heterocycles - Comins, D. L.; Joseph, S. P. (Alkaloid synthesis using 1-acylpyridinium salts as intermediates, 1996)

(untitled) - Comins, D. L.; LaMunyon, D. H.; Chen, X. (J. Org. Chem., 1997)

(untitled) - Comins, D. L.; Libby, A. H.; Al-awar, R. S.; Foti, C. J. (J. Org. Chem., 1999)

(untitled) - Kuethe, J. T.; Comins, D. L. (Org. Lett., 2000)

(untitled) - Pays, C.; Mangeney, P. (Tetrahedron Lett., 2001)

(untitled) - Bennasar, M. L.; Zulaica, E.; Ramírez, A.; Bosch, J. (J. Org. Chem., 1996)

(untitled) - Bennasar, M. L.; Vidal, B.; Bosch, J. (J. Org. Chem., 1996)

(untitled) - Amann, R.; Spitzner, D. (Angew. Chem., Int. Ed. Engl., 1991)

Chemistry of Heterocyclic Compounds: Pyridine and its Derivatives - Lyle, R. E. (Part B. Partially Reduced Pyridines, 1974)

(untitled) - Goldman, S.; Stoltefuss, J. (Angew. Chem., Int. Ed. Engl., 1991)

(untitled) - Sunkel, C. E.; Fau de Casa-Juana, M.; Santos, L.; Mar Gomes, M.; Villarroya, M.; Gonzalez-Morales, M. A.; Priego, J. G.; Ortega, M. P. (J. Med. Chem., 1990)

(untitled) - Jaing, J.-L.; Li, A.-H.; Jang, S.-Y.; Chang, L.; Melman, N.; Moro, S.; Ji, X.-d.; Lobkovsky, E.; Clardy, J.; Jacobson, K. A. (J. Med. Chem., 1999)

(untitled) - Mateeva, N. N.; Wineld, L. L.; Redda, K. K. (Curr. Med. Chem., 2005)

(untitled) - Ito, S.; Satoh, A.; Nagatomi, Y.; Hirata, Y.; Suzuki, G.; Kimura, T.; Satow, A.; Maehara, S.; Hikichi, H.; Hata, M.; Kawamoto, H.; Ohta, H. (Bioorg. Med. Chem., 2008)

(untitled) - Jones, P.; Griffin, A. M.; Gawell, L.; Lavoie, R.; Delorme, D.; Roberts, E.; Brown, W.; Walpole, C.; Xiao, W.; Boulet, J.; Labarre, M.; Coupal, M.; et al. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Liras, S.; McHardy, S. F.; Allen, M. P.; Segelstein, B. E.; Heck, S. D.; Bryce, D. K.; Schmidt, A. W.; Vanase-Frawley, M.; Callegari, E.; McLean, S. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Chowdhury, M. A.; Abdellatif, K. R. A.; Dong, Y.; Knaus, E. E. (Bioorg. Med. Chem., 2008)

(untitled) - Misra, M.; Pandey, S. K.; Pandey, V. P.; Pandey, J.; Tripathi, R.; Tripathi, R. P. (Bioorg. Med. Chem., 2009)

(untitled) - Krishna, P. R.; Reddy, P. S. (J. Comb. Chem., 2008)

(untitled) - Scott, J. D.; Li, S. W.; Wang, H. W.; Xia, Y.; Jayne, C. L.; Miller, M. W.; Duffy, R. A.; Boykow, G. C.; Kowalski, T. J.; Spar, B. D.; Stamford, A. W.; Chackalamannil, S.; et al. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Bosch, J.; Bennasar, M. L. (Synlett, 1995)

(untitled) - Bennasar, M.-L.; Alvarez, M.; Lavilla, R.; Zulaica, E.; Bosch, J. (J. Org. Chem., 1990)

(untitled) - Bennasar, M.-L.; Zulaica, E.; Jiménez, J. M.; Bosch, J. (J. Org. Chem., 1993)

(untitled) - Alvarez, M.; Salas, M.; de Veciana, A.; Lavilla, R.; Bosch, J. (Tetrahedron Lett., 1990)

(untitled) - Amat, M.; Linares, A.; Bosch, J. (J. Org. Chem., 1990)

(untitled) - Bennasar, M.-L.; Zulaica, E.; Ramírez, A.; Bosch, J. (Tetrahedron, 1999)

(untitled) - Bennasar, M.-L.; Vidal, B.; Bosch, J. (Chem. Commun., 1996)

(untitled) - Bennasar, M.-L.; Vidal, B.; Bosch, J. (J. Org. Chem., 1997)

(untitled) - Le Men, J.; Taylor, W. I. (Experientia, 1965)

(untitled) - Bennasar, M.-L.; Jiménez, J.-M.; Sufi, B. A.; Bosch, J. (Tetrahedron Lett., 1996)

(untitled) - Bennasar, M.-L.; Vidal, B.; Sufi, B. A.; Bosch, J. (Chem. Commun., 1998)

(untitled) - Albrecht, U.; Preuss, A.; Schmidt, A.; Fischer, C.; Langer, P. (Heterocycles, 2010)

(untitled) - Schmidt, A.; Michalik, D.; Rotzoll, S.; Ullah, E.; Fischer, C.; Reinke, H.; Görls, H.; Langer, P. (Org. Biomol. Chem., 2008)

(untitled) - Schmidt, A.; Gütlein, J.-P.; Preuss, A.; Albrecht, U.; Reinke, H.; Langer, P. (Synlett, 2005)

(untitled) - Ullah, E.; Rotzoll, S.; Schmidt, A.; Michalik, D.; Langer, P. (Tetrahedron Lett., 2005)

(untitled) - Yawer, M. A.; Hussain, I.; Gütlein, J.-P.; Schmidt, A.; Jiao, H.; Reinke, H.; Spannenberg, A.; Fischer, C.; Langer, P. (Eur. J. Org. Chem., 2008)

(untitled) - Karapetyan, V.; Mkrtchyan, S.; Schmidt, A.; Gütlein, J. P.; Villinger, A.; Reinke, H.; Jiao, H.; Fischer, C.; Langer, P. (Org. Biomol. Chem., 2008)

(untitled) - Schmidt, A.; Gütlein, J.-P.; Mkrtchyan, S.; Görls, H.; Langer, P. (Synlett, 2007)

(untitled) - Schmidt, A.; Gütlein, J.-P.; Langer, P. (Tetrahedron Lett., 2007)

(untitled) - Moghaddam, F. M.; Mirjafary, Z.; Saeidian, H.; Taheri, S.; Khodabakhshi, M. R. (Tetrahedron Lett., 2010)

(untitled) - Moghaddam, F. M.; Mirjafary, Z.; Saeidian, H.; Taheri, S.; Doulabi, M.; Kiamehr, M. (Tetrahedron, 2010)

(untitled) - Moghaddam, F. M.; Mirjafary, Z.; Saeidian, H.; Taheri, S.; Soltanzadeh, B. (Tetrahedron, 2010)

(untitled) - Moghaddam, F. M.; Taheri, S.; Mirjafary, Z.; Saeidian, H.; Kiamehr, M.; Tafazzoli, M. (Helv. Chim. Acta, 2011)

(untitled) - Moghaddam, F. M.; Saeidian, H.; Kiamehr, M.; Mirjafary, Z.; Taheri, S. (ARKIVOC, 2010)

(untitled) - Moghaddam, F. M.; Taheri, S.; Mirjafary, Z.; Saeidian, H. (Synlett, 2010)

(untitled) - Li, H.; Yan, C.-G. (Tetrahedron, 2011)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

Gaussian 09, Revision A.1 (Gaussian, Inc., 2009)

(untitled) - Kiamehr, M.; Moghaddam, F. M.; Gormay, P. V.; Semeniuchenko, V.; Villinger, A.; Langer, P.; Iaroshenko, V. O. (Tetrahedron, 2012)

Exploring chemistry with electronic structure methods - Foresman, J. B.; Frish, A. (Gaussian, Inc., 1993)

Thermochemistry in Gaussian - Ochterski, J. W.

(untitled) - Semeniuchenko, V.; Exner, T. E.; Khilya, V.; Groth, U. (Appl. Organomet. Chem., 2011)

(untitled) - Meza, R.; Gordillo, B.; Galván, M. (Int. J. Quantum Chem., 2005)